2014
DOI: 10.1016/j.ydbio.2014.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and molecular cues for cell outgrowth during C. elegans uterine development

Abstract: The Caenorhabditis elegans uterine seam cell (utse) is an H-shaped syncytium that connects the uterus to the body wall. Comprising nine nuclei that move outward in a bidirectional manner, this synctium undergoes remarkable shape change during development. Using cell ablation experiments, we show that three surrounding cell types affect utse development: the uterine toroids, the anchor cell and the sex myoblasts. The presence of the anchor cell (AC) nucleus within the utse is necessary for proper utse developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 102 publications
(101 reference statements)
0
22
0
Order By: Relevance
“…However, loss of lin-29 does not cause any detectable abnormality in Sp-Ut valve core morphology ( Fig 5A). Moreover, it has been reported that anchor cell invasion genes (fos-1, mig-10, egl-43, cdh-3, and zmp-1) are involved in utse development (Ghosh and Sternberg, 2014), but we did not observe any abnormality in the Sp-Ut valve upon RNAi knockdown of these genes (data not shown). Nevertheless, it will be interesting to examine whether the physical connection between the hypodermal seam and gonadal utse is formed properly in lin-28(lf) hermaphrodites.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, loss of lin-29 does not cause any detectable abnormality in Sp-Ut valve core morphology ( Fig 5A). Moreover, it has been reported that anchor cell invasion genes (fos-1, mig-10, egl-43, cdh-3, and zmp-1) are involved in utse development (Ghosh and Sternberg, 2014), but we did not observe any abnormality in the Sp-Ut valve upon RNAi knockdown of these genes (data not shown). Nevertheless, it will be interesting to examine whether the physical connection between the hypodermal seam and gonadal utse is formed properly in lin-28(lf) hermaphrodites.…”
Section: Discussionmentioning
confidence: 48%
“…The utse connects the uterus to the seam cells laterally and also to uv1 and vulva cells. egl-13:GFP is expressed in the nuclei of π cell lineage, whose products includes the utse, from late L3 to L4 stages (Ghosh and Sternberg, 2014). Utse labeled by egl-13:GFP migrated laterally in wild-type hermaphrodites (Fig S4A,B).…”
Section: Sp-ut Valve Morphogenesis Uterus Lumen Formation and Utse mentioning
confidence: 99%
“…The utse connects the uterus to the seam cells laterally and also to uv1 and the vulva. egl-13p::GFP is expressed in the nuclei of π cell lineage, the products of which include the utse cells, from late L3 to L4 stages (Ghosh and Sternberg, 2014). Utse cells labeled by egl-13p::GFP migrated laterally in wild-type hermaphrodites (Fig.…”
Section: Defects In Ovulation and Spermathecal Exit Cause Reduced Embmentioning
confidence: 98%
“…The uterus itself comprises the ut1-ut4 uterine toroid cells and du cells that together form a tube to hold eggs. Eggs pass from the uterus into the vulva through a junction comprising the uterine seam (utse) and uterine-ventral (uv1 and uv3) cells, and the vulva itself comprises several types of vulval toroid (vt) cells (Schindler and Sherwood, 2014;Ghosh and Sternberg, 2014;Ecsedi et al, 2015).…”
Section: Cells Of the Egg-laying Systemmentioning
confidence: 99%